Detection of the deformed wing virus of bees using the polymerase chain reaction: a review with reference to method performance. Issue 4 (7th August 2020) - Mataragka, Antonia; Leetham, Shannon; Smyth, Cassie S.; Decaro, Nicola; Charistos, Leonidas; Bouga, Maria; Ikonomopoulos, John
Abstract : The honey bee is of fundamental significance for the ecological balance of the planet and in effect, global crop and animal production. In recent years, the Deformed wing virus (DWV) has been recognised as a major threat to bees, causing an infection that can result in high colony losses. Effectively, the accurate detection of the pathogenic types of the specific virus acquires key-significance. The polymerase chain reaction (PCR) has been used for this purpose by many research groups. The specific technology confers speed and sensitivity but is delicate and prone to false reactions. In this respect, it was considered significant to conduct a review of the PCR methods developed to this day for the detection of the DWV, in order to assess their efficiency for their potential use in practice. The record of the reports that were selected to be included in this study consists only of those that are described with reference to pre-, and post-analytical evaluation, and have been reported more than once in the literature, by the team that developed them and others. The relevant publications were organised in seven groups consisting of the reports that refer to the application, the optimisation and/or the validation of the protocols developed originally by an equal number of research teams. This review is concluded with suggestions deducted from the result of the analysis, about how the limitations of the relevant research conducted to this day could be overcome.